Dedicated Spiral Breast Computed Tomography With a Single Photon-Counting Detector: Initial Results of the First 300 Women. Issue 2 (February 2020) - Berger, Nicole; Marcon, Magda; Frauenfelder, Thomas; Boss, Andreas
Abstract : Objectives: The aim of this study was to describe our initial clinical experiences using a dedicated spiral breast computed tomography (B-CT) with a single photon-counting detector. Materials and Methods: This retrospective study was approved by the institutional review board. Examinations of 300 consecutive women undergoing B-CT were evaluated on reason of assignment for B-CT instead of mammography, detection rate of breast cancer, and quality criteria of data acquisition. Further evaluated performance indicators were the number of additional ultrasounds examinations due to unclear findings or dense breast tissue and reliability of the technical data acquisition. Results: Five hundred ninety-one B-CT acquisitions in 300 women were performed. The main reason for preference of B-CT over mammography was the lack of breast compression (254 of 300, 84.7%), which was desired due to personal reasons or mastodynia, whereas 10 patients (0.3%) had implants hampering mammography. One hundred two possible lesions were detected in B-CT including 4 cases of breast cancer (1.3% of all patients). Additional ultrasound was performed in 226 patients (102 due to detected lesions and 124 due to dense breast tissue). Three malignant lesions were only detected in an additional ultrasound (1% of all patients). As a quality criterion, the pectoralis muscle was included in 341 of 591 examinations, but complete assessment of breast tissue was only possible in 149, respectively 140 examinations. No movement artifacts were noted. In 99% of all women, the examination could be realized. Conclusions: The dedicated B-CT provides high-quality images. It can be used as alternative particularly in those patients not otherwise willing to perform mammography because of the breast compression.